Quantitative Voltammetry in Weakly Supported Media: Effects of the Applied Overpotential and Supporting Electrolyte Concentration on the One Electron Oxidation of Ferrocene in Acetonitrile - Limon-Petersen, J; Streeter, I; Rees, N; Compton, R (2009)
Chronoamperometry is reported on the one electron oxidation of 3 mM ferrocene in acetonitrile using a 300 (± 5 μm radius gold hemisphere electrode. Varying concentrations of supporting electrolyte (tetra- nbutylammonium perchlorate) are used ranging from the fully supported (100 mM) to the almost completely unsupported (0.1 mM). The response is simulated using the Nernst-Plank-Poisson system of equations and excellent agreement between theory and experiment noted, so vindicating a recent theory (J. Phys. Chem. C, 2008, 112, 13716) for voltammetry in weakly supported media. © 2009 American Chemical Society.